Project-Based Learning as a catalyst for Students and Teacher Autonomy development: The experience in a State School in Nilo, Cundinamarca. - Agudelo, Jose Fabian; Morales Vasco, Adriana María (GIST – Education and Learning Research Journal, 2019)
This paper reports the findings of a graduation thesis which intended to identify the effects that Project-Based Learning implementation had on the development of autonomy of a group of tenth grade English language learners and their teacher. In this Action Research study, several instruments were used. An initial questionnaire to confirm perceptions; a student´s attitude scale to assess how students worked, both individually and in small groups; small group conferencing, which enabled students to speak about their projects; a teacher-research journal with teacher´s reflections on the implementation and effectiveness of the action strategies; and students´ journals containing reflections on the different stages of the process. The data gathered showed that PBL work led to both learners and their teacher having more positive attitudes and behaviors towards their own academic activities and teaching practice, respectively. This methodology encouraged learners to become decision makers, to gain responsibility and confidence, and to raise awareness of their role in the classroom, while also promoting the development of several features of the teacher´s teaching style. Thus, knowledge in the classroom was built cooperatively.